Current Population Survey, November 1989: Unemployment Benefit Compensation Supplement ([Verlag nicht ermittelbar], 2002)
This collection provides data on labor force activity for the week prior to the survey. Comprehensive data are available on the employment status, occupation, and industry of persons 15 years old and over. In addition, unemployed persons were asked a series of supplemental questions about unemployment compensation. The purpose of this supplement was to determine why a growing proportion of the unemployed were not receiving or had not been applying for benefits under the unemployment insurance program. Supplement questions focused on whether respondents had applied for unemployment benefits and whether they had received them since their last job, whether they had received an unemployment check in the week prior to the interview, reasons for not receiving unemployment compensation within the previous week, reasons respondents had not received unemployment compensation since their last job, and reasons for not applying for unemployment compensation. About a quarter of the unemployed respondents were asked the supplemental questions each month. These were respondents 15 years and older who reported either that they did not work in the previous week but had been working before and planned to begin a new job within 30 days, or were laid off, or looking for work. Unemployed persons who were trying to find employment for the first time were not considered eligible for the supplement. Personal characteristics such as age, sex, race, marital status, veteran status, household relationship, educational background, and Spanish origin are also included in the file.